THE CHALLENGES OF HIGNER EDUCATION IN THE CONTEXT OF REMOTE STUDIES: LEGAL REGULATION AND PRACTICE - Kudeikina, Inga; Zīvarts, Juris; Mihailovs, Ivans Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Technologies are becoming an integral component of study process. Opportunities brought by digitalisation in the field of education are not at variance with the right to education and conform to the right to exploit the achieved scientific and technical progress for enhancing human life and welfare; moreover, there no grounds for asserting that knowledge and skills acquired remotely are at a lower level than the results of face-to-face learning. However, to develop a uniform understanding and create a stable legal basis for the evolution of remote studying, legislative amendments that would define remote studying and set forth related requirements are needed.The aim of the research is the analysis of remote studies as a form and practice of education, evaluating the provisions of regulatory enactments in order to find out its admissibility and compliance with the right to education.The research uses document analysis, as well as methods of interpretation of legal norms and induction-deduction method, drawing conclusions and making proposals for improving regulatory enactments and practice of higher education establishments.However, there exist various interpretations of the content of remote studies. The management of higher education establishments are also discussing the construction of the term ‘contact hour’ provided in the Law on Higher Education Institutions, including remote studying that at least partially duplicates distance and open learning and additional requirements concerning the organisation of the remote study process.